The spectroscopic quadrupole moment of the 21+ state of 12C: A benchmark of theoretical models - J. Saiz-Lomas; M. Petri; I.Y. Lee; I. Syndikus; S. Heil; J.M. Allmond; L.P. Gaffney; J. Pakarinen; H. Badran; T. Calverley; D.M. Cox; U. Forsberg; et al. (Physics Letters B, 2023)
The spectroscopic quadrupole moment of the first 2+ state of 12C has been measured employing the Coulomb-excitation re-orientation technique. Our result of Qs(21+)=+9.3−3.8+3.5efm2 suggests a larger oblate deformation than previously reported. Combining this with the consistently re-analyzed adopted value, we present the most precise value to date of Qs(21+)=+9.5(18)efm2, which is consistent with a geometrical rotor description. This simple outcome is compared to state-of-the-art shell-model, mean-field, ab initio calculations, cluster-based and geometrical-like theories, which show varying degrees of emergent quadrupole collectivity.